Designing Cities. - Ridenour, Deena; Alizadeh, Tooran (Palgrave Macmillan, 2020)
The design of cities is an intentional act that fundamentally shapes the urban form of our cities, towns and neighbourhoods. The chapter defines the practice of urban design and describes the design process, and how it is implemented through policy and projects. It then explains how the design process is underpinned by foundational design elements and an understanding of the city as a historical construct, constantly evolving and influenced by past urban theories and models. A discussion of current urban design practice and emerging approaches to human-centred and ecological urbanism lead to a conclusion that speculates on the need for new design inventions with more collaborative approaches and interdisciplinary partnerships to address the challenges facing contemporary cities.
Keywords: Stadtentwicklung; Stadtdesign; Planungsprozess; Stadtgestaltung; Urbanismus